2019
DOI: 10.1371/journal.ppat.1007597
|View full text |Cite|
|
Sign up to set email alerts
|

15-keto-prostaglandin E2 activates host peroxisome proliferator-activated receptor gamma (PPAR-γ) to promote Cryptococcus neoformans growth during infection

Abstract: Cryptococcus neoformans is one of the leading causes of invasive fungal infection in humans worldwide. C . neoformans uses macrophages as a proliferative niche to increase infective burden and avoid immune surveillance. However, the specific mechanisms by which C . neoformans manipulates host immunity to promote its growth during infection remain ill-defined. Here we demonstrate that eicosanoid lipid mediator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…Deletion of Δplb1 has previously been shown to exhibit increased cell size during infection of macrophages in vitro and in a mouse model of cryptococcosis (25,26). We have recently demonstrated that several phenotypes associated with plb1 deletion were due to differences in fungal eicosanoid production, differences also present in a second cryptococcal mutant strain lac1 (27). We first wanted to ensure enlarged cryptococcal size also occurs in the zebrafish infection model; we measured the size of Δplb1 and Δlac1 cryptococcal cells at 1dpi, and found that there was a significant increase in cell diameter compared to wild type, with a 100% increase in the number of cryptococci with a diameter >5µm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of Δplb1 has previously been shown to exhibit increased cell size during infection of macrophages in vitro and in a mouse model of cryptococcosis (25,26). We have recently demonstrated that several phenotypes associated with plb1 deletion were due to differences in fungal eicosanoid production, differences also present in a second cryptococcal mutant strain lac1 (27). We first wanted to ensure enlarged cryptococcal size also occurs in the zebrafish infection model; we measured the size of Δplb1 and Δlac1 cryptococcal cells at 1dpi, and found that there was a significant increase in cell diameter compared to wild type, with a 100% increase in the number of cryptococci with a diameter >5µm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The C. neoformans variety grubii strain KN99, its GFP-expressing derivative KN99:GFP and mCherry-expressing derivative KN99:mCherry were used in this study (39). We used GFP expressing Δplb1-H99, Δlac1-H99 or parental H99-GFP (27) and Δgsc, Δsmt, Δsld8 and parental strain (24). Cultures were grown in 2□ml of yeast extract peptone dextrose (YPD) (all reagents are from Sigma-Aldrich, Poole, UK unless otherwise stated) inoculated from YPD agar plates and grown for 18□hours at 28□°C, rotating horizontally at 20□rpm.…”
Section: Methods and Methodsmentioning
confidence: 99%
“…Mice were randomised into treatment groups using the Google random number generator. Animals were infected by intranasal inoculation -mice were lightly anaesthetised using gaseous isofluorane and inoculated with 50μl of either 50,000cfu Cryptococcus neoformans KN99α GFP (18) or H99 ∆Plb1 GFP (42,43) or 50,000 6μm Fluoresbrite® YG Microspheres Polysciences (Hamburg, Germany). 0hpi mice were sacrificed by pentobarbital injection and exsanguination following recovery from the intranasal dosing anaesthesia.…”
Section: Mouse Infectionsmentioning
confidence: 99%
“…Long term 24hr imaging was done using a widefield Nikon Ti (Kingston Upon Thames, UK), imaged at 20x using the settings, lens and camera described in Evans et al (43). All data was captured using NIS element AR software.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation